Penggunaan Model Pembelajaran Picture And Picture Terhadap Aktivitas Sabilul Mubtadi’in Randegansari Driyorejo Gresik - Ainul Fithriyah; Nurul Agustin (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
This research was motivated by the results of initial observations showing that there was low activity in learning science in class IV at MI Sabilul Mubtadi'in. This is because teachers still use old methods of teaching, and most often use the lecture method, so that students become passive. With this, researchers are encouraged to create active, creative and fun learning by involving students with a problem focus: a) Application of the Picture and Picture learning model, b) Student learning activities in the application of the Picture and Picture learning model. This research uses the type of Classroom Action Research (PTK) with the subject being 28 students in class IV MI Sabilul Mubtadi'in Randegansari. The results of this research show that the application of the Picture and Picture learning model succeeded in increasing the percentage of student activity by 43.75%, namely from 50% in cycle I to 93.75% in cycle II. Student affective and psychomotor assessment, with an average percentage in cycle I of 75% and an increase in cycle II of 94%, and assessment of students' skills in using the Picture and Picture Learning Model with an average percentage in cycle I of 78%, an increase in cycle II it was 89%. Thus it can be concluded that the Picture and Picture learning model can increase student activity.